Faktor Risiko Demam Berdarah di Negara Tropis - Zata Ismah; Tri Bayu Purnama; Dyah Retno Wulandari; Ema Rizka Sazkiah; Yulia Khairina Ashar (ASPIRATOR - Journal of Vector-borne Disease Studies, 2021)
Tropical countries are the largest contributor to the incidence of Dengue HemorrhagicFever (DHF), but research on risk factors is still independent in various countries, it cannot beconcluded holistically. Through the research design, a systematic review is able to summarize andanswer the causes of DHF in this tropical country. This research method is a systematic review withguidelines following the 2009 PRISMA Checklist. In the initial search, 1,680 articles were foundusing the keyword “risk factors for Dengue Hemorrhagic Fever”, reduced to 274 article titles afteradding the keyword “tropical country”. Furthermore, the relevant abstracts were fi ltered and found37 selected article items. Through critical appraisal of the full text of the article, it was found that 17articles met the selection criteria for further review in this study. The results showed that there were5 major groups of risk factors that were widely studied, namely sociodemography, climatology, placeof dwelling, environment, and behavior. The sociodemographic factor associated with the incidenceof DHF in tropical countries is age. In terms of climatology, temperature and rainfall are importantfactors in the vector breeding process. Rural areas (rural areas) are the place of dwelling with the mostcases of DHF found. The environmental aspect that has been widely studied is mosquito breeding. Themost signifi cant risk behavior factor in transmission was the behavior of hanging clothes. Of the 17articles, it was found that 77.8% of the articles examined environmental variables.